How Social Media Shapes Green Purchase Intention among Generation Y and Z - Nurrahma, Rizky Amalia; Sugiarto, Catur (Dinasti International Journal of Education Management and Social Science, 2025)
This study examines how social media influences green purchase intention among Generation Y and Z consumers in Indonesia through egoistic motivation and perceived green value. Using PLS-SEM analysis on 311 respondents aged 18-42 years, the research reveals that social media positively affects green purchase intention both directly (β=0.118, p<0.05) and indirectly through egoistic motivation (β=0.141, p<0.001) and perceived green value (β=0.305, p<0.001). Perceived green value demonstrates stronger mediating effects than egoistic motivation, explaining 53.3% variance in purchase intention. These findings suggest that marketers should leverage social media platforms in ways that resonate with the emotional and social aspects of their audiences, encouraging more sustainable consumption among digitally-connected younger generations.